Bridging the skills gap in remote sensing and GIS: insights from the ReSENSE project - Prodromou, Maria; Gkounti, Eleni; Gitas, Ioannis; Georgopoulos, Nikos; Georgiou, George; Georgiou, Fotini; Kyprianou, Maria; Hadjimitsis, Diofantos G. (My University, 2025)
Identifying Geographic Information Systems (GIS) and Remote Sensing (RS) as indispensable tools underscores the critical demand for skilled professionals in land-use mapping, urban morphology analysis, vegetation monitoring, and disaster management. Despite this demand, the lack of experts limits the effective application of these technologies in both academic and professional contexts. The Remote Sensing Technology Training (ReSENSE) project, funded by Erasmus+, aims to bridge this gap by providing targeted vocational education and training in Cartography, RS, GIS, Copernicus Services and Image Processing including emerging technologies such as cloud computing, Information and Communication Technologies ICT), the Internet of Things (IoT), Machine Learning (ML), and Artificial Intelligence (AI). This study presents key findings from a comprehensive survey conducted in Cyprus and Greece, assessing the training needs of professionals in environmental and governmental sectors. To address these challenges, ReSENSE offers accessible, hands-on training opportunities both in person and remotely to meet the growing demand in the industry. It is vital to enhance participants’ educational experience through upskilling and reskilling. By making these resources widely available, the project enhances professional competencies, fosters career advancement, and expands opportunities in sectors that increasingly rely on GIS and RS technologies.
Keywords: Remote sensing; GIS; Vocational Training; Skills Development